The role of sex steroids in white adipose tissue adipocyte function. Issue 4 (April 2017) - Newell-Fugate, A E
Abstract : With the increasing knowledge that gender influences normal physiology, much biomedical research has begun to focus on the differential effects of sex on tissue function. Sexual dimorphism in mammals is due to the combined effects of both genetic and hormonal factors. Hormonal factors are mutable particularly in females in whom the estrous cycle dominates the hormonal milieu. Given the severity of the obesity epidemic and the fact that there are differences in the obesity rates in men and women, the role of sex in white adipose tissue function is being recognized as increasingly important. Although sex differences in white adipose tissue distribution are well established, the mechanisms affecting differential function of adipocytes within white adipose tissue in males and females remain largely understudied and poorly understood. One of the largest differences in the endocrine environment in males and females is the concentration of circulating androgens and estrogens. This review examines the effects of androgens and estrogens on lipolysis/lipogenesis, adipocyte differentiation, insulin sensitivity and adipokine production in adipocytes from white adipose tissue with a specific emphasis on the sexual dimorphism of adipocyte function in white adipose tissue during both health and disease.